Application of The Small Group Discussion Method to Student Learning Motivation in Citizenship Subjects - Ardana, Mira Shaila; Pane, Arifah S Zidana; Aulia, Dinda; Al Karim Rambe, Rahmansyah Fadlul (International Journal of Cultural and Social Science, 2024)
Small group discussion is a learning method that is carried out by students and consists of between 4 to 6 people so as to form small groups to achieve more effective learning goals. The application of this learning method was researched in order to increase student enthusiasm, especially in learning activities in civics subjects. The method used in this study is the library research method, namely by collecting data sourced from books, journals, and internet sites. The results of this study are as follows: how to form the right discussion groups and the benefits obtained in implementing small group discussions so as to increase students' interest in civics subjects.